2018
DOI: 10.1111/efp.12465
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of white pine blister rust on limber pine in Colorado and Wyoming

Abstract: Cronartium ribicola is a non‐native, heteroecious, fungal pathogen that causes white pine blister rust (WPBR) on all white pines, including Pinus flexilis James (limber pine). The pathogen continues to move southwards and eastwards in the Rocky Mountains of Colorado and Wyoming on populations of limber pine. We examined the progression and intensification of WPBR on limber pine in recently invaded areas (<40 years) by combining historical accounts of disease occurrence with recent large‐scale monitoring projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…In support of this, we found that our maturity index variable was the 4th most important variable for reducing model error in our first mortality model and contributed significantly to predicting live trees. Other important life‐history traits may include vulnerability to host‐specific pathogens— P. monticola and P. albicaulis; for example, both had high recent and future mortality rates and previous research implicates bark beetles and white pine blister rust as major contemporary disturbances throughout the range of these species (Geils et al 2010, Jacobi et al 2018). Alternatively, some species or populations may currently be in the midst of a widespread dieback due to anthropogenic climate change that is pushing them past critical environmental stress tolerance thresholds despite apparently normal mortality for the ecosystem or region (Huang et al 2015, Kolb 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, we found that our maturity index variable was the 4th most important variable for reducing model error in our first mortality model and contributed significantly to predicting live trees. Other important life‐history traits may include vulnerability to host‐specific pathogens— P. monticola and P. albicaulis; for example, both had high recent and future mortality rates and previous research implicates bark beetles and white pine blister rust as major contemporary disturbances throughout the range of these species (Geils et al 2010, Jacobi et al 2018). Alternatively, some species or populations may currently be in the midst of a widespread dieback due to anthropogenic climate change that is pushing them past critical environmental stress tolerance thresholds despite apparently normal mortality for the ecosystem or region (Huang et al 2015, Kolb 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our results somewhat agree with previous work that suggests future forest mortality may be a widespread phenomenon, but we emphasize that some species and regions may be disproportionately affected (Allen et al 2010, Kane et al 2014, McDowell and Allen 2015). Future efforts to mitigate the effects of anthropogenic climate change should focus on active management or conservation of key species or populations, and future efforts to model mortality risk in western U.S. forests should emphasize plant functional traits or physiology common to vulnerable species, such as current efforts to control white pine blister rust in P. monticola and P. albicaulis (Geils et al 2010, Jacobi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Spread of WPBR has been extensive on both coasts of North America, yet in some areas of the US Rocky Mountains and southwest, including Colorado, Utah, Nevada, Arizona and New Mexico, the pathogen has only recently been introduced or is not yet present (Blodgett & Sullivan, 2004; Cleaver et al, 2015; Goodrich et al, 2018; Jacobi et al, 2018; Schoettle et al, 2018; Vogler, Geils, et al 2017; Vogler, Maloney, et al 2017). Protection of white pine species is vital as they provide many ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…Like all other North American white pines, P. strobiformis is very susceptible to the disease white pine blister rust (Conklin et al, 2009;Sniezko et al, 2011). However, the fungal pathogen is a more recent invader of the southwestern United States, detected in the Sacramento Mountains of New Mexico in 1990 (Hawksworth, 1990) with a likely earlier arrival in the 1970s (Jacobi et al, 2018), and has not yet been identified within the pine's core range in Mexico. Unease about the potential impacts of increasing incidence of rust in P. strobiformis forests, along with projected increasing aridity and range contraction in the southern portion of the species range (Seager and Vecchi, 2010;Shirk et al, 2018), have led to an increased interest in what type and frequency of genetic resistance may naturally occur in the species.…”
Section: Introductionmentioning
confidence: 99%